2013
DOI: 10.1155/2013/280392
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Swertisin fromEnicostemma littoraleDifferentiates NIH3T3 Cells into Islet-Like Clusters and Restores Normoglycemia upon Transplantation in Diabetic Balb/c Mice

Abstract: Aim. Stem cell therapy is one of the upcoming therapies for the treatment of diabetes. Discovery of potent differentiating agents is a prerequisite for increasing islet mass. The present study is an attempt to screen the potential of novel small biomolecules for their differentiating property into pancreatic islet cells using NIH3T3, as representative of extra pancreatic stem cells/progenitors. Methods. To identify new agents that stimulate islet differentiation, we screened various compounds isolated from Eni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Enicostemma littorale, a perennial herb, has been used for therapy of diabetes mellitus in India as a folk medicine (Saranya et al 2013). Very recently we also demonstrated that EL MeOH extract possess potential islet neogenic activity from tissue specific stem/progenitor cells, which was later confirmed by identifying the active ingredient swertisin for this islet neogenic potential in a another recent report from us (Dadheech et al 2010(Dadheech et al , 2013. There are also other reports where decrease in insulin resistance, normalization of fat and carbohydrate metabolism by EL were observed in both experimental cellular and rodent models (Maroo et al 2002;Vasu et al 2003;Patel et al 2013).…”
Section: Discussionsupporting
confidence: 57%
“…Enicostemma littorale, a perennial herb, has been used for therapy of diabetes mellitus in India as a folk medicine (Saranya et al 2013). Very recently we also demonstrated that EL MeOH extract possess potential islet neogenic activity from tissue specific stem/progenitor cells, which was later confirmed by identifying the active ingredient swertisin for this islet neogenic potential in a another recent report from us (Dadheech et al 2010(Dadheech et al , 2013. There are also other reports where decrease in insulin resistance, normalization of fat and carbohydrate metabolism by EL were observed in both experimental cellular and rodent models (Maroo et al 2002;Vasu et al 2003;Patel et al 2013).…”
Section: Discussionsupporting
confidence: 57%
“…Further, the author's research group is continuously involved in exploring the wide spectrum hidden potentials of this plant for islet neogenesis and various diabetic complications [15, 22, 23]. Qualitative analyses of EL have demonstrated the presence of flavonoids and secoiridoid glycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has well documented Enicostemma littorale Blume owing antioxidant, hypolipidemic, and antidiabetic activities both in animals and human diabetic patients [13, 14]. Apart from antidiabetic activity, islet neogenic property of swertisin and normoglycemia in a diabetic rat are also reported [15]. Hence, it can be presumed that the EL extract potentially owes varied beneficiary activities due to the presence of many compounds within it.…”
Section: Introductionmentioning
confidence: 99%
“…The most studied transcription factors (pancreatic and duodenal homeobox factor-1, neurogenin 3 and musculoaponeurotic fibrosarcoma oncogene family protein A) are expressed in β-cell precursors, which have a role in inducing differentiation and in maintaining the functionality of the β-cells (Kaneto et al, 2007). The most important obstacles to the clinical use of these transcription factors, as well as of the above-mentioned hormones and growth factors, are represented by their high costs and low efficiency in obtaining functional βcells clusters (Dadheech et al, 2013). Thus, in these circumstances, POMs have been proposed as alternative, effective molecules.…”
Section: Polyoxometalates Stimulated Differentiation Of Stem Cells Inmentioning
confidence: 99%